Clouds of Illusion in the Aesthetics of Nature. (18th June 2013) - Zangwill, Nick
<x xml:space="preserve">Abstract</x> I defend extreme formalism about the aesthetics of inorganic nature. I outline the general issue over aesthetic formalism as it manifests itself in the visual arts. The main issue is over whether we need to know about the history of artworks in order to appreciate them aesthetically. I then turn to nature and concede that with organic nature we need to know a thing's biological kinds if we are fully to appreciate it. However, with in organic nature I deny that we need to know the deeper nature of the things we experience. What is important, I argue, are the appearances of those things not their real natures. I consider the beauty of clouds, which depends on an illusion of solidity, and I argue that scientific knowledge does not reveal beauty that is not available to the ignoramous. There is only the beauty of appearances, and it does not matter whether those appearances are accurate or illusory.